2020
DOI: 10.1186/s12877-020-01606-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting non-elective hospital readmission or death using a composite assessment of cognitive and physical frailty in elderly inpatients with cardiovascular disease

Abstract: Background: We aimed to assess the utility of the combination of the mini-mental state examination (MMSE) + clock drawing test (CDT) and the Fried phenotype for predicting non-elective hospital readmission or death within 6 months in elderly inpatients with cardiovascular disease (CVD). Methods: A single-center prospective cohort was conducted from September 2018 to February 2019. Inpatients ≥65 years old were recruited. Predictive validity was tested using a Cox proportional hazards regression model analysis,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…Frailty is of particularly concern for patients with HF. HF put the repeatedly exposes geriatric patients to stress and vulnerability, and the prevalence of frailty is higher in these patients than in the general older adults, which may be associated with depression, disability, and cognitive impairment [ 6 8 ]. According to the process of HF development [ 9 ], HF is divided into four stages of A (preHF), B (preclinical HF), C (clinical HF), and D (refractory HF).…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is of particularly concern for patients with HF. HF put the repeatedly exposes geriatric patients to stress and vulnerability, and the prevalence of frailty is higher in these patients than in the general older adults, which may be associated with depression, disability, and cognitive impairment [ 6 8 ]. According to the process of HF development [ 9 ], HF is divided into four stages of A (preHF), B (preclinical HF), C (clinical HF), and D (refractory HF).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment exerts a detrimental effect on prognosis among older communitydwelling adults [31]. This same effect was observed in patients hospitalized in the cardiology department for acute heart failure or any cardiac cause at 6 months and 1-year follow-up [32][33][34]. Likewise, cognitive impairment diagnosed during hospitalization influenced in-hospital and 1-year mortality in acute myocardial infarction patients [4][5][6][7].…”
Section: Prognosis Impactmentioning
confidence: 74%
“…One possible reason for this inconsistency may be that we excluded patients with dementia from our study, and only patients with mild cognitive decline were enrolled, and thus there was an insufficient number of cases with CVD to detect early changes in cognitive function. Second, previous studies have found that some forms of CVD and risk factors, such as heart failure ( Yao et al, 2020 ), coronary artery disease ( Ma et al, 2020 ), stroke ( Chumha et al, 2020 ), atrial fibrillation ( Guo et al, 2020 ), and obesity ( Chan et al, 2020 ), are significantly associated with frailty, thus the relationship between CVDs or risk factors and MCI may be weakened in frail patients. Further research on CVDs and MCI in frail patients should be performed in the future.…”
Section: Discussionmentioning
confidence: 99%